Sharing economy - Orr, Tamra (Global citizens: social media., 2019)
Highlights the history of the idea of being a sharing economy in which citizens share things ranging from community bikes and scooters to ride sharing apps and Uber, and explores related issues. Includes resources for further information, a glossary, and color photographs.